2018
DOI: 10.1108/ict-04-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Followership under the spotlight: implications for followership development

Abstract: Purpose -The leadership industry has experienced an unprecedented growth in popularity, and business management effectiveness has become synonymous with leaders' roles. However, in this egalitarian twenty-first century little mention has been made of followership due to its negative stereotype. The purpose of this paper is to contribute to the understanding of followership by presenting a "balanced" approach that views both leaders and followers as co-producers of leadership. Specific practical implications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Given these and other scholarly findings that followers are larger contributors to organizational outcomes than previously believed (Bufalino, 2018; Carsten et al , 2010; Uhl-Bien et al , 2014), it stands to reason that follower development should be as important to organizations as leader development. As described below, one government agency embraced this concept as it sought to enhance employee empowerment and role in decision-making by developing follower skills.…”
Section: The Emergence Of Followership Developmentmentioning
confidence: 87%
See 1 more Smart Citation
“…Given these and other scholarly findings that followers are larger contributors to organizational outcomes than previously believed (Bufalino, 2018; Carsten et al , 2010; Uhl-Bien et al , 2014), it stands to reason that follower development should be as important to organizations as leader development. As described below, one government agency embraced this concept as it sought to enhance employee empowerment and role in decision-making by developing follower skills.…”
Section: The Emergence Of Followership Developmentmentioning
confidence: 87%
“…As noted earlier, in every day interaction, leading and following are fluid states impacted by situational realities similar to those expressed in the contingency theory (Bass, 2008; Northouse, 2013; Yukl, 2010). In other words, people often take on a leader or follower role as the situation dictates (Carsten et al , 2014; Bufalino, 2018; Stech, 2008). Additionally, scholars have found that appointed leaders in an organization typically serve as followers of senior leaders, corporate boards or even have instances of following someone more junior in the hierarchy (Baker et al , 2014; Bjugstad et al , 2006; Morris, 2014).…”
Section: Incorporating Followership Into a Leadership Development Programmentioning
confidence: 99%
“…Considering "the cult of leadership" (Manning and Robertson, 2016), embedding followership training within leader development may appear leader-centric (Oc and Bashshur, 2013). However, if Bufalino's (2018) vision of followership becoming mainstream is the goal, this approach is strategic as it leverages wellestablished leader-development activities.…”
Section: Coaching/mentoringmentioning
confidence: 99%
“…In the conclusion, recommendations for developing followership are offered. Meeting Bufalino's (2018) goal for followership development to be embedded in leadership programs, all recommendations were designed to be part of existing leadertraining activities. The proceeding section explains how IFTs, gender-role stereotypes and transformational leadership support the connections between female caregiving and beliefs about followers.…”
mentioning
confidence: 99%
“…treating followership as having equal value to leadership; focusing on followership development through training and mentoring ;and measuring learned followership skills (Bufalino, 2018;Hurwitz and Hurwitz, 2015).…”
Section: Introductionmentioning
confidence: 99%